Solid-phase synthesis of N-trichloroacetyl mannosamine 1-phosphate repeating units mimicking capsular polysaccharide derived from Neisseria meningitidis serotype A. (August 2022) - Sato, Kazuki; Chiba, Akie; Shiraishi, Tomomi; Ogawa, Yuki; Hara, Rintaro Iwata; Wada, Takeshi
Abstract: N -Trichloroacetyl analogs of N -acetylmannosamine 1-phosphate repeating units, which are found in capsular polysaccharides of Neisseria meningitidis serotype A, were successfully obtained via solid-phase synthesis using an oxazaphospholidine monomer. The introduction of the trichloroacetyl group into the amino group of mannosamine resulted in the stabilization of the reaction intermediates. Monosaccharide, disaccharide, and tetrasaccharide derivatives were obtained and isolated. This is the first example to demonstrate the synthesis of the N -acylated mannosamine 1-phosphate structure having no less than four phosphate linkages. Graphical abstract: Image 1 Highlights: N -Trichloroacetyl analogs of N -acetylmannosamine 1-phosphate repeating units were obtained. Solid-phase synthesis using an oxazaphospholidine monomer was conducted. Trichloroacetyl group stabilized the reaction intermediates. Monosaccharide, disaccharide, and tetrasaccharide derivatives were obtained and isolated.